Menopause-related cortical loss of the humeral head region mainly occurred in the greater tuberosity - Wang, Yeming; Li, Jian; Men, Yutao; Wei, Wanfu (Frontiers in Endocrinology, 2022)
Aims: proximal humerus fractures are commonly observed in postmenopausal women. The goal of this study was to investigate menopause-related changes in cortical structure of humeral head. Materials and Methods: Clinical computed tomography (CT) scans of 75 healthy women spanning a wide range of ages (20-72 years) were analyzed. For each subject, cortical bone mapping (CBM) was applied to create color 3D thickness map for proximal humerus. Nine regions of interest (ROI) were defined in three walls of humeral head. Cortical parameters, including the cortical thickness (CTh), cortical mass surface density (CM), and the endocortical trabecular density (ECTD) were measured. Results: Compared to the premenopausal women, postmenopausal women were characterized by a significantly lower CTh and CM value in the lateral part of the greater tuberosity. Similar changes were only found in ROI 4, but not in ROI5-6 in the less tuberosity. Linear regression analysis revealed that the CTh and CM value of ROI 1, 3, 4 were negatively associated with age. These results showed that menopause-related loss in cortical thickness and cortical mass surface density was mainly in the greater tuberosity, besides the proximal part of lesser tuberosity. Trabecular bone variable measured as ECTD showed a notable lower in ROI1-9 in post-menopausal versus pre-menopausal group. Inverse linear associations for ECTD and age were found in ROI 2, 3, 5,6,7,9, indicating no site-specific differences of endocortical trabecular loss between the greater and lesser tuberosity. Conclusions menopause-related cortical loss of the humeral head mainly occurred in the lateral part of the greater tuberosity. The increased rate of humeral bone loss in the greater tuberosity may contribute materially to complex proximal humerus fracture.